Description of the initial approach to patients with suspected child abuse in the emergency department of a pediatric hospital - Diana A. Guerrero-Reséndiz; María T. Gómez Chavarría; Víctor Olivar-López; Magdalena Cerón-Rodríguez; Mónica Villa-Guillén; Horacio Márquez-González (Permanyer, 2022)
Background: Child abuse is one of the leading causes of morbidity and mortality worldwide. This study aimed to identify whether the approach to the diagnosis of child abuse was comprehensive in a tertiary care hospital. Methods: We conducted a retrospective study of patients with a final diagnosis of child abuse admitted through the emergency department. Results: A total of 73 confirmed cases were analyzed. We observed a predominance of female patients (65.8%). Physical abuse was the most common type of abuse (80.8%). Complete blood count and a nutritional status analysis were recorded in 100% of the patients and coagulation times in 43%; however, no patient had a thorough bone series study. Conclusions: According to the evidence found in medical records, gaps were detected in the approach to patients with suspected child abuse upon arrival at the emergency department. For this reason, all areas where pediatric medical care is provided should have tools that offer agility and ease of diagnosis.